PENGGUNAAN HAK ANGKET DPRD KABUPATEN MEMPAWAH TERKAIT APBD KABUPATEN MEMPAWAH TAHUN 2020-2021 BERDASARKAN PERATURAN TATA TERTIB DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN MEMPAWAH NOMOR. 1 TAHUN 2020,TENTANG TATA TERTIB DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN MEMPAWAH. - A. RAfik NIM. A1012161128 (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACT Regional heads (regents and/or deputy regents) in carrying out their duties based on the authority granted by laws and regulations, along with these duties and authorities are carried out by the People's Legislative Assembly in their area, in this case the DPRD. This DPRD has supervisory duties in carrying out governance based on the General Principles of Good Governance to create a prosperous society. This supervisory function is regulated in Article 159 of Law Number 23 of 2014 concerning Regional Government namely;